Control strategy and simulation verification of hardware-in-the-loop system of automotive steering device. Issue 1 (July 2020) - Zhen, Yajing; Wang, Zhaojian; Liu, Jiawei; Guan, Tian; Zhang, Yaoming; Wang, Mengen; Song, Xiaoli; Zhang, Dongsheng
Abstract: As one of the key technologies of intelligent assisted driving simulation, hardware-in-the-loop control system has gradually become the focus of attention. Driverless has gradually become a hot topic. This paper designs a hardware-in-the-loop system of the steering device, that is, the steering device and the software system form a closed loop. This paper studies two control strategies including manual driving and driverless driving. This hardware-in-the-loop system is designed by the upper computer and controlled by the lower computer. The communication between the steering wheel and the upper computer is realized through the serial communication protocol. This hardware-in-the-loop system can simulate two modes of manual driving and driverless driving, and a visual interface is made on the display screen, which can effectively analyse the steering in real time. It provides a basic platform for the research of automobile steering and driverless driving.